Das Römische Heerwesen: auch im 21. Jahrhundert Gegenstand intensiver Forschung - Wesch-Klein, Gabriele (Studia Europaea Gnesnensia, 2017)
History of the Roman army – in a broad sense – was one of the pillars of Géza Alföldy’s scholarly studies and investigations. His inspiring interpretations of various inscriptions had a fundamental impact on the shape of contemporary science. He was particularly interested in such issues as religion of the Roman military, the origins of soldiers, the rules of promotion and the careers of officers with senatorial and equestrian lineage. The article offers an overview of major studies in history of the Roman army published in the recent years. There is no doubt that many had been inspired by the work and writings of Géza Alföldy. Although it is merely a subjective selection, the list of publications appended to the article attests to the intensity of such research, showing that it truly flourishes. Strictly speaking, Géza Alföldy did not come up with any novel research problems as far as the Roman military was concerned. He would address those which had been present in science, as it is documented by works of such scholars as Alfred von Domaszewski, Konrad Kraft, Emil Ritterling, Eric Birley or Arthur and Ernst Stein. Nonetheless, Géza Alföldy understood the essence and appreciated the need to pursue those studies in greater depth while utilizing epigraphy to the broadest possible extent. Quite rightly, he considered inscriptions to be the foremost sources in that respect. Guided by hic saxa loquntur as his motto, Alföldy determined the shape of methodology employed in studies of the Roman army through his work. The ordinary soldiers and officers became genuine individuals, which in a sense enabled one to gain insight into their personal lives, professional careers, family ties, and religious beliefs. Thus far, research in the two first decades of the 21st century follows the same path. It may only be desired that, as a result, the current state of our knowledge will be substantially enriched.